Groovy and Grails Recipes - Abdul-Jawad, Bashar (Apress, 2012)
Java, the platform, is going to stay around for quite a while. Java the language, however, is beginning to show its age, and it’s time now for Java developers to start thinking in terms of dynamic languages. Groovy is one of the best dynamic languages available for the Java platform. After years of working with Groovy, I am firmly convinced that all Java developers should at least give Groovy a try. The amount of coding you can save with a dynamic language like Groovy is really amazing—especially when working with collections or files. It is for this reason that I decided to write this book. I want to share this great increase in productivity that I gained with Groovy with the large number of Java developers out there. Dynamic languages such as Groovy made web frameworks like Grails a reality. Grails is a breath of fresh air for Java developers and it is one of the main reasons why I became so interested in dynamic languages. I remember that my first days of Java web development were with Struts and Tapestry. And boy, I don’t miss those days. To me, those frameworks always seemed unnecessarily complex, and I just couldn’t stand the amount of configuration and boilerplate code you had to write to get anything done. That’s not what frameworks are supposed to do. Frameworks are supposed to make your tasks easier and let you focus on the logic of the problem at hand, which is exactly what Grails does. Grails makes sense, which is to me the number one feature I look for in any new technology. Grails is such a simple, and yet powerful, framework that you can’t help but wonder why no one thought of it earlier.